H. G. WELLS, GEOLOGY, AND THE RUINS OF TIME. Issue 4 (8th November 2017) - Shackleton, David
Abstract : H. G. Wells's The Time Machine (1895) has hitherto been read in two principal scientific contexts: those of evolutionary biology and thermodynamic physics. Numerous critics have situated the romance in the context of evolutionary biology and contemporary discourses of degeneration (McLean 11–40; Greenslade 32–41). Others have discussed it in the context of thermodynamic physics. For instance, Bruce Clarke has read The Time Machine as "a virtual allegory of classical thermodynamics, " and shows that its combination of physical and social entropy reflects a wider transfer within the period of concepts and metaphors from physical science to social discourses of degeneration (121–26). Neatly linking these scientific contexts with issues of form, Michael Sayeau has argued that the social and physical entropy that are themes of the romance are reflected in its narrative structure, which manifests a type of narrative entropy, and thereby raises the spectre of the end of fiction (109–46).